2011
DOI: 10.1016/j.fbp.2010.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the growth of Arthrospira (Spirulina) platensis from Toliara (Madagascar): Effect of agitation, salinity and CO2 addition

Abstract: Arthrospira (Spirulina) platensis Toliara isolated from alkaline and salt lakes in the southwestern area of Madagas car is a potential source of proteins that could efficiently fight against food deficiency in developing countries like Madagascar. Up to now, productivity in this country has been low, so a better understanding of the growth condi tions of this species is needed to improve its production. Growth experiments were undertaken in bubble columns at laboratory scale. The influence of agitation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
4
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 28 publications
7
25
4
5
Order By: Relevance
“…Air agitation seemed to be 41 more efficient. These results are in agreement with that obtained by Ravelonandro et al (2011) who found that agitation of the culture, medium salinity (ranging from 13 to 35 g L -1…”
Section: Pond Maintenancesupporting
confidence: 83%
“…Air agitation seemed to be 41 more efficient. These results are in agreement with that obtained by Ravelonandro et al (2011) who found that agitation of the culture, medium salinity (ranging from 13 to 35 g L -1…”
Section: Pond Maintenancesupporting
confidence: 83%
“…The latter finding is in agreement with the results reported by Rabelo et al (2013), Selmo and Salas-Mellado (2014), and Shahbazizadeh et al (2014), who have found that Spirulina enrichment increases the protein content of the final products. The Spirulina powder used in our trials contained 62.9% (w/w) of protein, thereby increasing the protein content of croissants (Ravelonandro et al 2011). Besides being a rich source of protein, Spirulina also contains several minerals and vitamins, including vitamin B 12 (Danesi et al 2010;Minh 2014).…”
Section: Resultsmentioning
confidence: 99%
“…En un experimento que los referidos autores denominan de larga duración (100h), encontraron que tanto la tasa de crecimiento como la morfología de la Spirulina, son sensibles a los estímulos mecánicos del fluido y, que una aplicación de 100h de tensión mecánica sobre la Spirulina, puede llevar a la adaptación de la función fotosintética y de su morfología; que la tasa de crecimiento depende del esfuerzo cortante, el cual proporciona a las microalgas un estímulo físico. Asimismo, Ravelonandro et al (2011) encontraron que las células de Spirulina son frágiles y, en una columna de burbujas sin mezclado adicional existe un mejor crecimiento, confirmando su sensibilidad al esfuerzo cortante. En este sentido en la presente investigación, la alta turbulencia podría haber estimulado a una adaptación de la fotosíntesis, adicionalmente a los efectos lumínicos observados en los fotoperiodos de 12/12 y 24/0 h L/O.…”
Section: Pruebas Hidráulicas Con Agua Corriente En Fotobiorreactor Deunclassified
“…En este sentido en la presente investigación, la alta turbulencia podría haber estimulado a una adaptación de la fotosíntesis, adicionalmente a los efectos lumínicos observados en los fotoperiodos de 12/12 y 24/0 h L/O. Ravelonandro et al (2011) sostienen que la columna de burbujas, parece ser el sistema más adecuado para el estudio del crecimiento de Spirulina en escala de laboratorio, así como a gran escala. En este sentido en la presente investigación, el flujo del cultivo estuvo basado en un sistema de columna de burbujas, que produjo un ε entre ar y ab generando turbulencia por el movimiento del cultivo en el FB-BCAA.…”
Section: Pruebas Hidráulicas Con Agua Corriente En Fotobiorreactor Deunclassified